Safety, effectiveness and tolerability of sublingual ketamine in depression and anxiety: A retrospective study of off-label, at-home use - Hassan, Kazi; Struthers, William M.; Sankarabhotla, Aditya; Davis, Patrick (Frontiers in Psychiatry, 2022)
Intravenous and intranasal ketamine have been shown to be effective therapeutic options in patients suffering from treatment-resistant depression (TRD). The use of sublingual (SL), rapid dissolve ketamine tablets (RDT) offers a novel approach for delivery for mental health indications. This study assessed the effectiveness and safety of self-administration of off-label, SL, rapid dissolve ketamine tablets (RDT) at-home for depression and anxiety. Intake scores on the Generalized Anxiety Disorder Screener (GAD-7) and Patient Health Questionnaire (PHQ-9) were compared to scores after treatments of three doses of ketamine RDT, and then six doses of ketamine RDT. After three doses of SL ketamine, 47.6% of patients showed a significant decrease in PHQ-9 scores, and 47.6% of patients showed a significant reduction in GAD-7 scores. Reduction rates were similar in those with initial Moderate to Severe symptoms, and higher in those patients who then completed a clinically recommended six doses of RDT ketamine. This study demonstrates that SL ketamine is a novel, safe, and effective treatment for TRD and treatment-resistant anxiety. SL ketamine offers an alternative therapeutic approach to IV ketamine when treating those with TRD.